Effect of drill speed during drilling of human cadaveric tibiae - Fernandes, M.G.A. (2018)
Bone fracture is a feature of everyday life. Most of the treatments involve bone drilling to fixation of implanted medical devices. Bone loss due to excessive produced heat during drilling may weaken the purchase of surgically placed screws and pins, causing them to loosen postoperatively. Decrease the heat generation has a great demand as it helps in better fixation and healing of bone tissue. This paper presents an experimental model to study the effect of drill speed using human cadaveric tibiae. The results revealed that the temperature rise and the duration of temperature elevation decreased when lower drill speeds are used.